Fundamentals of financial management - Brigham, Eugene F. , 1930-; Houston, Joel F. (South-Western Cengage Learning, 2009)
Intends to ensure an understanding of corporate finance and financial management. This title presents a foundation in financial basics punctuated with examples, end-of-chapter applications, and Integrated Cases that make it easier to understand the how and why of corporate budgeting, financing, and working capital decision making